Cellulolytic yeast from gastrointestinal tract of muscovy duck (Anas moscata) as probiotic candidate - Anggraeni, A.S.; Istiqomah, L.; Damayanti, E.; Anwar, M.; Sakti, A.A.; Karimy, M.F. (Diponegoro University, 2018)
Cellulose is one of limiting factors in local poultry feed. Yeast exploration of local poultry gastrointestinal tract and its utilization as a probiotic candidate has not been widely studying. A total of 112 isolates of yeast were obtained from the digestive tract of Muscovy Duck, Javanesse Duck and Indonesian Native Chicken in the small intestine, cecum, and colon. Yeast with cellulolytic activity was quantitatively selected using CYG agar + 1% CMC medium with an incubation time of 30 ° C for 48 hours under anaerobic conditions. A total of 107 isolates of yeasts have cellulolytic activity. M41 yeast isolates of Mentok cecum possess highest clear zones cellulolytic activity (0.64 cm). M41 yeast characterization includes molecular identification, growth ability testing in CMC and glucose combination medium, CMCase activity, and viability test of probiotic ability with time variation. The results showed that yeast M41 had 98% proximity with Saccharomyces cerevisiae based on 26S sRNA gene sequence analysis, optimum growth on medium containing 1% CMC and 0.1% glucose (b / v), CMCase activity of 42.98 U / mL, and has a viability of 91.91; 66.22; 42.00; 42.00; 1.83 and 42.13 (%) respectively on bile salts 2 hours and 3 hours, gastric juice 45 minutes and 2 hours, pH 2 and pH 3 for 90 minutes. Based on results of the study, it was concluded that S. cerevisiae M41 potentially as a probiotic candidate for poultry with cellulolytic activity.